2018
DOI: 10.1111/jocn.14545
|View full text |Cite
|
Sign up to set email alerts
|

The effectiveness of extended care based on Internet and home care platform for orthopaedics after hip replacement surgery in China

Abstract: Internet and home care orthopaedic platform is a nursing system designed specifically for extended care management outside of the hospital, which is helpful for patients who undergone hip replacement to obtain effective home care services after discharge, improving patients' quality of life and rehabilitation efficacy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
42
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(49 citation statements)
references
References 20 publications
5
42
0
Order By: Relevance
“…Eventually, 17 articles23–39 from 14 studies with in total 2494 participants were included. An overview of extracted data of the included studies can be found in online supplementary material 4.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Eventually, 17 articles23–39 from 14 studies with in total 2494 participants were included. An overview of extracted data of the included studies can be found in online supplementary material 4.…”
Section: Resultsmentioning
confidence: 99%
“…Fifteen of the included articles from 12 studies described randomised controlled trials,23 24 26–33 35–39 while two articles described controlled before-after studies 25 34. Most studies were conducted in high-income countries (ie, Western Europe, USA or Australia) and two studies in China38 39 studying samples of patients undergoing surgeries to their back (ie, laminectomy, lumbar discectomy, disc surgery and spinal stenosis),23 24 26 28–31 34 39 upper limbs (ie, anterior shoulder dislocation repair),25 37 hips (ie, total hip arthroplasty)33 36 38 and knees (ie, ACL reconstruction and knee arthroplasty) 27 32 35. Patient samples consisted of combinations of men and women, and the average age of the study samples ranged from 29 to 70 years, with an average (SD) of 51 (14) years.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the effects of WeChat health education on outcomes first increased and then decreased. Several limited studies intended to improve the self‐management of patients and deliver health education via a social networking platform have shown the long‐term effectiveness (Wang et al, ). Thus, studies on maintaining the long‐term effects of health education programmes in haemodialysis patients are suggested for future research.…”
Section: Discussionmentioning
confidence: 99%
“…Several limited studies intended to improve the self-management of patients and deliver health education via a social networking platform have shown the long-term effectiveness (Wang et al, 2018).…”
Section: Discussionmentioning
confidence: 99%